Сиреневая даль: [стихи] / Виталий Иродов - Иродов Виталий Олегович (Удмуртия, 2017)
Экземпляры: ф.1 (20171005) / Инвентарный номер: 57656 / Цена: / Сис.шифр: 84(2Рос=Удм)6-5 / Авт.знак: И 83 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Удм)6-5